m6A modification associated with YTHDF1 is involved in Japanese encephalitis virus infection - Xiao-han Li; Jing Chen; Yu-da Ou; Xiang Zhong; Jia-huan Hu; Rui-cong Sun; Ying-jun Lv; Jian-chao Wei; Yun Young Go; Bin Zhou (Veterinary Microbiology, 2023)

Molecular and functional characterization of golden pompano (Trachinotus blochii) TBK1 on IFN regulation - Jin-Feng Tong; Rui-Hai Gan; Lang Yu; Shao-Yang Bu; Jun-Long Sun; Xin Wen; Fei-Biao Song; Li Zhou; Jian-Fang Gui; Jian Luo (Fish & Shellfish Immunology, 2023)

Peripheral BDNF Regulates Somatosensory–Sympathetic Coupling in Brachial Plexus Avulsion-Induced Neuropathic Pain - Hang Xian; Huan Guo; Yuan-Ying Liu; Jian-Lei Zhang; Wen-Chao Hu; Ming-Jun Yu; Rui Zhao; Rou-Gang Xie; Hang Zhang; Rui Cong (Neuroscience Bulletin, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Constituents of the fruits of Rubus chingii Hu and their neuroprotective effects on human neuroblastoma SH-SY5Y cells - Jingyi Wang; Xue Zhang; Jundong Yu; Jun Du; Xiaohong Wu; Liang Chen; Rui Wang; Yingchun Wu; Yiming Li (Food Research International, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Ferrostatin-1-loaded thermosensitive nanodelivery system for noise-induced hearing loss treatment - Peng-Wei Ma; Pei-Heng Lu; Hao Yuan; Jia-Wei Chen; Wei Gao; Yu-Qiang Lun; Jia-Ning Guo; Xue-Rui Ding; Rui Liang; Si-Yu Li; Zi Wang; Wei-Long Wang; et al. (Chemical Engineering Journal, 2023)

Constructing MoS2-SnS heterostructures on N-doped carbon nanosheets for enhanced catalytic conversion of polysulfides in lithium-sulfur batteries - Junpu Zhang; Wen Xi; Feng Yu; Youfang Zhang; Rui Wang; Yansheng Gong; Beibei He; Huanwen Wang; Jun Jin (Chemical Engineering Journal, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Leaf senescence, nitrogen remobilization, and productivity of maize in two semiarid intercropping systems - Wei Wang; Meng-Ying Li; Rui Zhou; Fei Mo; Aziz Khan; Asfa Batool; Wei Zhang; Jun-Sheng Lu; Ying Zhu; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; et al. (European Journal of Agronomy, 2023)

Epoxy-based high-k composite vitrimer: With low dielectric loss, high breakdown strength and surface electrical damage repairability - Yu-Cheng Zhang; Wen-Dong Li; Xin Zhao; Fan-Bo Meng; Peng Sun; Chao Wang; Guang-Zhi Guo; Wen-Rui Li; Guan-Jun Zhang (Chemical Engineering Journal, 2023)

Astragaloside IV-mediated inhibition of oxidative stress by upregulation of ghrelin in type 2 diabetes–induced cognitive impairment - Rui-hua Zhang; Shan-shan Cao; Yong Shi; Xin Wang; Lei-lei Shi; Yu-han Zhang; Chao-jun Han; Bin Wang; Liang Feng; Ji-ping Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Comparative transcriptome profiling reveals RNA splicing alterations and biological function in patients exposed to occupational noise - Jia-Wei Chen; Jun-Jie Shao; Shao-Fei Zhao; Pei-Heng Lu; Si-Yu Li; Hao Yuan; Peng-Wei Ma; Yu-Qiang Lun; Wei-Long Wang; Rui Liang; Wei Gao; Qian Yang; et al. (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Numeric and nonnumeric information input to predict adsorption amount, capacity and kinetics of tetracyclines by biochar via machine learning - Bai-Qin Zhou; Rui-Chun Yang; Hui-Ping LI; Yu-Jun Wang; Chun-Yue Zhang; Zi-Jie Xiao; Zhong-Qi He; Wei-Hai Pang (Chemical Engineering Journal, 2023)

Investigating the electrochemical performance of MnO2 polymorphs as cathode materials for aqueous proton batteries - Yujie Dai; Jianze Zhang; Xiaorong Yan; Guoqing Zhao; Mingsheng Yang; Jiakui Xiong; Rui Li; Naihua Miao; Haiping Yu; Mingjun Hu; Jingru Liu; Jun Yang (Chemical Engineering Journal, 2023)

Punicalagin relieves lipotoxic injuries on pancreatic β-cells via regulating the oxidative stress and endoplasmic reticulum stress-mediated apoptosis - Ning Wang; Kexin Yang; Jun Wang; Jinghe Liang; Shengbo Yu; Aiqing Zhu; Rui Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Analytical study on heavy metal output fluxes and source apportionment of a non-ferrous smelter in southwest China - Chenchen Li; Peng Dong; Jin Yan; Rui Gong; Qi Meng; Jun Yao; Hanjing Yu; Yaoqiang Ma; Bang Liu; Ruosong Xie (Environmental Pollution, 2023)

Norethindrone suppress the germ cell development via androgen receptor resulting in male bias - Xiao-Bing Long; Wen-Jun Shi; Chong-Rui Yao; Si-Ying Li; Jin-Ge Zhang; Zhi-Jie Lu; Dong-Dong Ma; Yu-Xia Jiang; Guang-Guo Ying (Aquatic Toxicology, 2023)

The first homosporous lycophyte genome revealed the association between the recent dynamic accumulation of LTR-RTs and genome size variation - Ji-Gao Yu; Jun-Yong Tang; Ran Wei; Mei-Fang Lan; Rui-Chen Xiang; Xian-Chun Zhang; Qiao-Ping Xiang (Plant Molecular Biology, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Identification and characterization of a phosphinothricin N-acetyltransferase from Enterobacter LSJC7 - Feng Zhu; Yu Yan; Xi-mei Xue; Rui-lian Yu; Jun Ye (Pesticide Biochemistry and Physiology, 2023)

2,4-Dinitrotoluene (2,4-DNT) exposure induces liver developmental damage and perturbs lipid metabolism and oxygen transport gene expression in zebrafish (Danio rerio) - Liangxia Su; Hang Sha; Jun Liu; Le Yu; Huanhuan Li; Rui Wang (Environmental Science and Pollution Research, 2023)

Anti-hardening effect and mechanism of silkworm sericin peptide in high protein nutrition bars during early storage - Hongtao Zhu; Xiu-Xiu Zhang; Rui Zhang; Jing-Yu Feng; Kiran Thakur; Jian-Guo Zhang; Zhao-Jun Wei (Food Chemistry, 2023)

Abundant rather than rare fungi perform a vital role in maintaining the growth of continuous cropped cut chrysanthemum - Rui Tao; Jun Li; Siqi Yu; Baowei Hu; Ning Ling; Guixin Chu (European Journal of Soil Biology, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

A20 ameliorates disc degeneration by suppressing mTOR/BNIP3 axis-mediated mitophagy - Xin Peng; Cong Zhang; Jia-Wei Gao; Feng Wang; Jun-Ping Bao; Zhi-Min Zhou; Rui Sun; Hang-Yu Ji; Cabral VLF; Xiao-Tao Wu (Genes & Genomics, 2023)

Behaviour of FRP spiral-confined concrete and contribution of FRP longitudinal bars in FRP-RC columns under axial compression - Jun-Jie Zeng; Yu-Yi Ye; Wei-Te Liu; Yan Zhuge; Yue Liu; Qing-Rui Yue (Engineering Structures, 2023)

Comprehensive analysis of the fates and risks of veterinary antibiotics in a small ecosystem comprising a pig farm and its surroundings in Northeast China - Jian-yong Wu; Jun-min Gao; Jin-song Guo; Xian-yu Hou; De-rui Wang; Jing-cheng Wu; Xiao-jun Li; Chun-yun Jia (Journal of Hazardous Materials, 2023)

Individual tree segmentation and biomass estimation based on UAV Digital aerial photograph - Zhao Sun; Yi-fu Wang; Zhi-dan Ding; Rui-ting Liang; Yun-hong Xie; Rui Li; Hao-wei Li; Lei Pan; Yu-jun Sun (Journal of Mountain Science, 2023)

Microbial-induced calcium carbonate precipitation: Influencing factors, nucleation pathways, and application in waste water remediation - Yu Liu; Amjad Ali; Jun-Feng Su; Kai Li; Rui-Zhu Hu; Zhao Wang (Science of The Total Environment, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

The Impacts of Dietary Curcumin on Innate Immune Responses and Antioxidant Status in Greater Amberjack (Seriola dumerili) under Ammonia Stress - Chuanpeng Zhou; Zhong Huang; Shengjie Zhou; Jing Hu; Rui Yang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma (Journal of Marine Science and Engineering, 2023)
In this study, we investigated the effect of dietary curcumin on non-specific immune responses and antioxidative ability in Seriola dumerili under ammonia stress and post-recovery. Three diets were prepared to contain 0, 75, and 150 mg/kg of curcumin. A total of 225 greater amberjack (initial weight: 100.90 ± 0.03 g) were distributed into nine cylindrical tanks, constituting an experimental design with three treatments and three replicates. After 56 days of feeding, plasma, intestinal, and hepatic enzyme activities were evaluated. Then, an acute ammonia challenge experiment was conducted. Ten fish per tank were subjected to acute ammonia stress (total ammonia-N: 1000 mg/L) for eight minutes followed by six minutes of recovery. The results indicated that dietary curcumin significantly promoted intestinal and hepatic alkaline phosphatase (ALP) and acid phosphatase (ACP) levels as well as hepatic antioxidative enzymes such as superoxide dismutase (SOD), total antioxidant capacity (T-AOC), reduced glutathione (GSH), and glutathione peroxidase (GSH-Px) of greater amberjack. In addition, curcumin addition improved the activities of antioxidant enzymes, such as SOD, T-AOC, GSH, GSH-Px, and catalase (CAT), and reduced malondialdehyde (MDA) content in liver, spleen, head kidney, and brain tissues after post-recovery. The indexes related to immunity and antioxidant enzymes in the liver, gill, and spleen rose again to some extent, but they showed the worst recovery ability in the head kidney and brain tissue samples. These results indicate that dietary curcumin supplementation could increase non-specific immune responses, antioxidant ability, and enhance resistance to high ammonia stress in juvenile S. dumerili.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Construction of 3D Ni2+-Al3+-LDH/γ-Fe2O3-Cd2+-Ni2+-Fe3+-LDH structures and multistage recycling treatment of dye and fluoride-containing wastewater - Rui Dang; Xiang-Rong Ma; Yun-Peng Zhao; Menjiao Ren; Wei Guo; Yu-Hong Kang; Yong Gao; Shiqing Bi; Wenwen Gao; Hua-Rui Hao; Rui Bai; Yu-Fei Wang; et al. (Chemical Engineering Journal, 2023)